If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x(x + 5) = 0 Reorder the terms: 3x(5 + x) = 0 (5 * 3x + x * 3x) = 0 (15x + 3x2) = 0 Solving 15x + 3x2 = 0 Solving for variable 'x'. Factor out the Greatest Common Factor (GCF), '3x'. 3x(5 + x) = 0 Ignore the factor 3.Subproblem 1
Set the factor 'x' equal to zero and attempt to solve: Simplifying x = 0 Solving x = 0 Move all terms containing x to the left, all other terms to the right. Simplifying x = 0Subproblem 2
Set the factor '(5 + x)' equal to zero and attempt to solve: Simplifying 5 + x = 0 Solving 5 + x = 0 Move all terms containing x to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + x = 0 + -5 Combine like terms: 5 + -5 = 0 0 + x = 0 + -5 x = 0 + -5 Combine like terms: 0 + -5 = -5 x = -5 Simplifying x = -5Solution
x = {0, -5}
| 2x^2-20x=-42 | | y+5+2y= | | 6x+5x=63 | | 4(n-1)=-8 | | y^2+9y=-20 | | 5y-2(y+4)=1 | | 3x^2-8x^7-2x^2=9x^7 | | 6x^2-8x-12=0 | | 2K(K+3)=-9 | | 2K(K+3)=9 | | 3(x-4)+15=2(x+3) | | 6y^2-6=0 | | 5/12-7/8= | | 4x^2=4x | | -1/5-4(m+1/12)=39/10(m-11/6) | | a^2b^2-121=0 | | 9+-10x+x^4=0 | | x+6x-40=0 | | -10x+3+9x=-x-7 | | x^4-10x+9=0 | | 5v^3-65v^2+200v=0 | | 2x-7/3=-7 | | 8a+a= | | 6a+12=2a-6 | | 8a-3b+2a+6b= | | 3y+5y=9y | | m^2+9m+7=-5+9(-5)+7 | | 5x^2+10x=40 | | w^2+7w=8 | | 2w^2+6w=8 | | 4x^2=-9x-5 | | 3a^2+a+20=0 |